Reference values for the phase angle of the electrical bioimpedance: Systematic review and meta-analysis involving more than 250,000 subjects - Mattiello, Rita; Amaral, Mariana Azambuja; Mundstock, Eduardo; Ziegelmann, Patrícia Klarmann (Clinical nutrition (Edinburgh, Scotland), 2020)
The bioimpedence phase angle has been considered as a predictor for morbidity and mortality in different clinical situations, although reference values from a large healthy population are lacking. The aim of this meta-analysis is to estimate mean phase-angle values in healthy individuals. This meta-analysis systematically searched MEDLINE, EMBASE, The Cochrane Controlled Trials Register, SCIELO, LILACS, CINAHL, Web of Science and gray literature for studies estimating mean phase angles. Quality of evidence was assessed for all studies and subgroup (males and females) meta-analysis stratified by age group according to literature (up to 2; 3–5; 6–12; 13–15; 16–18; 19–28; 29–38; 39–48; 49–58; 59–69; 70–80 and >80 years of age) were conducted using random-effects models. A total of 46 studies including 249,844 subjects were selected for the present analysis. Males show a pooled estimate of the mean phase angle of 3.6 (95% CI: 3.0–4.1) for infants (0–2 y), increasing progressively to 7.3 (95% CI: 7.0–7.5) at the teenage phase (16–18 y), stabilizing during adult ages (18–38) and decreasing progressively with ongoing years with an estimate of 5.3 (95% CI: 4.5–6.0) for elderly above 80 years old. Similarly, females start from 3.7 (95% CI: 3.2–4.3) for infants (0–2 y), increasing progressively to 6.4 (95% CI: 6.1–6.8) at the teenage phase (16–18 y), stabilizing during adult ages (18–48) and decreasing progressively with ongoing years with an estimate of 5.4 (95% CI: 5.3–5.6) for elderly above 80 years old. Also, males have higher estimates than females for all age groups except for infants (0–2) and subjects older than 80 years old. Heterogeneity was high for all age groups. In both sexes, phase-angle values have a similar pattern that start from infants, increase progressively up to the teenage phase, stabilize during adult ages, and then decrease progressively in older subjects and the elderly. •Phase angle is a predictor of morbidity and mortality in different clinical situations. Nevertheless, reference values from a large healthy population data are lacking.•This study synthesizes data from 46 studies including 249,844 health individuals and provides estimates for mean phase angle for males and females stratified by age.•Phase-angle increases progressively from the first years of life until 18 years of age, then stabilizes from 19 until 48 years and progressively decreases with ongoing years.•This study provides references values that can contribute to the prediction of health status in clinical practice.